High cycle stability sodium ion battery positive electrode material and preparation method and application thereof

Preparation of the positive electrode material of copper, iron, manganese-based sodium ion battery co-doped Li and Al through high-temperature solid phase method, solving the problems of low cycle stability and low average working voltage of existing materials, and achieving high discharge specific capacity and median discharge value Voltage and excellent cycling stability.

CN119118207BActive Publication Date: 2025-02-25TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411636391.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing copper-iron-manganese-based sodium ion battery layered oxide positive electrode materials have problems with low cycling stability and low average working voltage.

Method used

The positive electrode material of copper, iron-manganese-based sodium ion battery co-doped Li and Al was prepared by high-temperature solid phase method, using P2 phase structures Cu, Fe, and Mn as the basic framework, and the unfavorable doping is suppressed by the coordinated doping of inactive Li and Al. Phase transition and lattice distortion.

Benefits of technology

The discharge specific capacity, discharge median voltage and cycling stability of the sodium ion battery are significantly improved, so that the sodium ion battery has high discharge specific capacity, discharge median voltage and excellent cycling stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention discloses a cathode material for a sodium-ion battery with high cycle stability, a preparation method thereof and an application. The preparation method includes: uniformly mixing a sodium source, a copper source, an iron source, a manganese source, a lithium source and an aluminum source to obtain a precursor powder. In terms of the number of moles, the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, manganese in the manganese source, lithium in the lithium source and aluminum in the aluminum source is 0.7035:0.06:0.33:(0.61 - x - y):1.05x:y, where 0 < x < 0.1 and 0 < y < 0.1; sintering the precursor powder and cooling it with the furnace to obtain a cathode material for a sodium-ion battery with high cycle stability. The cathode material for a sodium-ion battery with high cycle stability according to the present invention takes the P2-phase structure as the basic framework. By co-doping non-active Li and Al elements into the copper-iron-manganese-based material, lattice distortion and element mixing are effectively inhibited, and the discharge specific capacity, discharge median voltage and cycle stability of the sodium-ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material with high cycle stability, and a preparation method and application thereof. Background Art

[0002] In recent years, the shortage of lithium resources has caused the price of lithium-ion batteries to continue to rise. Sodium-ion batteries have an electrochemical working principle similar to that of lithium-ion batteries. Since sodium is abundant and easily available, sodium-ion batteries have significant cost advantages. In addition, the reserves of elements commonly used in sodium-ion batteries, such as iron, manganese, and aluminum, in the earth's crust are relatively high. These characteristics help reduce the cost of sodium-ion battery cathode materials and are conducive to the sustainable development of large-scale energy storage. Layered oxide cathode materials have the characteristics of high theoretical capacity, high energy density, high voltage, and simple preparation methods, and have received widespread attention from academia and industry.

[0003] Copper-iron-manganese-based sodium-ion battery layered oxide cathode materials have a high theoretical specific capacity and can provide a large energy storage capacity. Compared with other high-performance battery materials (such as cobalt and nickel), their main components (copper, iron, and manganese) are lower in cost, more abundant on Earth, and relatively environmentally friendly, which helps reduce dependence on scarce resources. However, they currently face problems of low capacity and poor stability.

[0004] The patent with publication number CN115611319A discloses a copper-iron-manganese-based layered oxide positive electrode material for sodium ion batteries. -1 At a current density of 1.5 %, its first discharge capacity can reach 130 mA h g -1 However, its cycle stability and average working voltage (i.e., median discharge voltage) are relatively low (20 mA g -1 At the current density, the capacity retention rate was 78% after 100 cycles, and the average working voltage was 3V).

[0005] The patent with publication number CN116259742A discloses a copper-iron-manganese-based layered oxide positive electrode material for sodium ion batteries, which has a high conductivity at 100 mA g -1 After 500 cycles at the current density, the capacity retention rate is 79%, and the cycle stability needs to be improved. Summary of the invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing a positive electrode material for a sodium ion battery with high cycle stability. The positive electrode material for a sodium ion battery with high cycle stability prepared by a high-temperature solid phase method is a copper-iron-manganese-based sodium ion battery positive electrode material co-doped with Li and Al with high capacity, high discharge median voltage and high cycle stability.

[0007] Another object of the present invention is to provide an application of the above-mentioned high cycle stability sodium ion battery positive electrode material in a sodium ion battery.

[0008] The purpose of the present invention is achieved through the following technical solutions.

[0009] A method for preparing a positive electrode material for a sodium ion battery with high cycle stability comprises the following steps:

[0010] S1, a sodium source, a copper source, an iron source, a manganese source, a lithium source and an aluminum source are mixed evenly to obtain a precursor powder. The ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, manganese in the manganese source, lithium in the lithium source and aluminum in the aluminum source is 0.7035:0.06:0.33:(0.61-xy):1.05x:y, wherein 0 <x<0.1,0<y<0.1;

[0011] In S1, x=0.08, y=0.08.

[0012] In S1, the sodium source is one or a mixture of sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate and sodium oxalate.

[0013] In S1, the copper source is one of copper acetate, copper oxide, copper carbonate, copper nitrate, copper chloride, copper oxalate, copper acetylacetonate, or a mixture of several thereof.

[0014] In S1, the iron source is one of iron acetate, iron oxide, iron carbonate, iron nitrate, iron chloride, iron oxalate, and iron acetylacetonate, or a mixture of several of them.

[0015] In S1, the manganese source is one of manganese acetate, manganese oxide, manganese carbonate, manganese nitrate, manganese chloride, manganese oxalate, and manganese acetylacetonate, or a mixture of several of them.

[0016] In S1, the lithium source is one of lithium acetate, lithium oxide, lithium carbonate, lithium nitrate, lithium chloride, lithium oxalate, lithium acetylacetonate, or a mixture of several of them.

[0017] In S1, the aluminum source is one of aluminum acetate, aluminum oxide, aluminum carbonate, aluminum nitrate, aluminum chloride, aluminum oxalate, and aluminum acetylacetonate, or a mixture of several of them.

[0018] In S1, a sodium source, a copper source, an iron source, a manganese source, a lithium source and an aluminum source are mixed and wet-ball-milled to be uniform.

[0019] In the above technical solution, the solvent for wet ball milling is acetone.

[0020] In the above technical solution, the rotation speed of the wet ball mill is 300~1400 rpm, and the time of the wet ball mill is 0.5~3 h.

[0021] In the above technical solution, the wet ball milling uses an alumina ball mill or a zirconia ball mill.

[0022] S2, sintering the precursor powder at 600-1000° C. for 2-24 hours, cooling along with the furnace, to obtain a positive electrode material for a sodium ion battery with high cycle stability. The sodium ion battery prepared from the positive electrode material for a sodium ion battery with high cycle stability has a discharge median voltage of 3-3.5 V and an energy density of 410-430 watt-hours per kilogram (Wh / kg).

[0023] In S2, the heating rate to 600~1000 ℃ is 3~5 ℃ / min.

[0024] In S2, sintering is preferably performed at 800-950°C for 2-24h.

[0025] The high cycle stability sodium ion battery positive electrode material obtained by the above preparation method.

[0026] The application of the above-mentioned high cycle stability sodium ion battery positive electrode material in improving the discharge specific capacity of the sodium ion battery.

[0027] The application of the above-mentioned high cycle stability sodium ion battery positive electrode material in improving the median discharge voltage of the sodium ion battery.

[0028] The application of the above-mentioned high cycle stability sodium ion battery positive electrode material in improving the cycle stability of sodium ion batteries.

[0029] The application of the above-mentioned high cycle stability sodium ion battery positive electrode material in improving the energy density of sodium ion batteries.

[0030] A sodium ion battery comprises a sodium ion battery positive electrode material with high cycle stability.

[0031] In the above technical solution, the sodium ion battery includes a liquid sodium ion battery and a solid sodium ion battery.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The high cycle stability sodium ion battery positive electrode material of the present invention is based on the P2 phase structure of Cu, Fe, Mn (copper-iron-manganese-based material) as the basic framework. By synergistically doping the copper-iron-manganese-based material with inactive Li and Al double elements, the adverse phase change of the copper-iron-manganese-based material in the electrochemical reaction and the lattice distortion and element mixing during the charge and discharge process are effectively suppressed. Under a higher charging voltage, the discharge specific capacity, discharge median voltage and cycle stability of the sodium ion battery are improved, so that the sodium ion battery has high discharge specific capacity, discharge median voltage and excellent cycle stability, and has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the XRD pattern of the high cycle stability sodium ion battery positive electrode material prepared in Example 1;

[0035] Figure 2 This is a SEM image of the high cycle stability sodium ion battery positive electrode material prepared in Example 1;

[0036] Figure 3 The charge and discharge curve of the sodium ion battery prepared in Example 3;

[0037] Figure 4 This is a cycle performance diagram of the sodium ion battery prepared in Example 3 at a current density of 1 C;

[0038] Figure 5 This is a cycle performance diagram of the sodium ion battery prepared in Example 3 at a current density of 2 C;

[0039] Figure 6 This is a cycle performance diagram of the sodium ion battery prepared in Example 3 at a current density of 5 C;

[0040] Figure 7 This is a cycle performance diagram of the sodium ion battery prepared in Example 3 at a current density of 10 C;

[0041] Figure 8 This is the XRD pattern of the high cycle stability sodium ion battery positive electrode material prepared in Example 2;

[0042] Fig. 9 This is a SEM image of the high cycle stability sodium ion battery positive electrode material prepared in Example 2;

[0043] Fig.10 The charge and discharge curve of the sodium ion battery prepared in Example 4;

[0044] Fig.11 This is a cycle performance diagram of the sodium ion battery prepared in Example 4 at a current density of 0.5 C;

[0045] Fig.12This is a cycle performance diagram of the sodium ion battery prepared in Example 4 at a current density of 1 C;

[0046] Fig.13 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 1;

[0047] Fig.14 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 1;

[0048] Fig.15 The charge and discharge curve of the sodium ion battery prepared in Comparative Example 4;

[0049] Fig.16 This is a cycle performance diagram of the sodium ion battery prepared in Comparative Example 4 at a current density of 1 C;

[0050] Fig.17 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 2;

[0051] Fig.18 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 2;

[0052] Fig.19 The charge and discharge curve of the sodium ion battery prepared in Comparative Example 5;

[0053] Fig. 20 This is a cycle performance diagram of the sodium ion battery prepared in Comparative Example 5 at a current density of 1 C;

[0054] Fig.21 This is the XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 3;

[0055] Fig. 22 This is a SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 3;

[0056] Fig.23 The charge and discharge curve of the sodium ion battery prepared in Comparative Example 6;

[0057] Fig.24 This is a cycling performance diagram of the sodium ion battery prepared in Comparative Example 6 at a current density of 1 C. DETAILED DESCRIPTION

[0058] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0059] The raw material information involved in the following examples is as follows:

[0060] The sodium source (sodium carbonate) was purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd., and the copper source (CuO), iron source (Fe2O3), manganese source (Mn2O3), lithium source (Li2CO3) and aluminum source (Al2O3) were purchased from McLean Reagent.

[0061] The XRD patterns were measured by an X-ray diffractometer (ARL EQUINOX 3000, Thermo Fisher Scientific) at 40 kV and 40 mA in the 2θ range of 10 to 80°;

[0062] Scanning electron microscope: Quanta FEG, USA.

[0063] The charge and discharge performance tests of the sodium ion batteries prepared in Examples 3-4 and Comparative Examples 4-6 were conducted on a blue-electric test system model CT 2001A produced by Wuhan Shenglan Electronic Technology Co., Ltd. When testing the discharge median voltage, the current density of the blue-electric test system was set to 0.2C.

[0064] 1C = 150mA g -1 .

[0065] Embodiment 1-2

[0066] A method for preparing a positive electrode material for a sodium ion battery with high cycle stability comprises the following steps:

[0067] S1, mix the sodium source, copper source, iron source, manganese source, lithium source and aluminum source, wet-mill at a speed of 1400 rpm for 2 h until uniform (alumina ball mill is used for wet milling, acetone is the solvent for wet milling, the volume fraction of the solvent and the amount of substance fraction of sodium in the sodium source is 25:1, the unit of volume fraction is mL, and the unit of amount of substance fraction is mol), dry in an oven at 80 ° C for 2 h to obtain a precursor powder, and the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, manganese in the manganese source, lithium in the lithium source and aluminum in the aluminum source is X, and the value of X is shown in Table 1. The sodium source is sodium carbonate, the copper source is copper oxide (CuO), the iron source is iron oxide (Fe2O3), the manganese source is manganese oxide (Mn2O3), the lithium source is lithium carbonate (Li2CO3), and the aluminum source is aluminum oxide (Al2O3);

[0068] S2, placing the precursor powder in a muffle furnace, heating it to 900°C at a rate of 5°C / min in an air atmosphere and sintering it at 900°C for 12 h, then cooling it to room temperature 20~25°C with the furnace to obtain a sodium ion battery positive electrode material with high cycle stability.

[0069] In Examples 1 and 2, Cu, Fe, and Mn are the main components of the basic framework of the P2 phase structure, and Li and Al doping will not change the phase structure of the positive electrode material of the sodium ion battery with high cycle stability.

[0070] Table 1

[0071]

[0072] Comparative Example 1

[0073] A sodium ion battery positive electrode material (Na 0.67 Cu 0.06 Fe 0.33 Mn 0.61 O2) preparation method, comprising the following steps:

[0074] S1, mixing a sodium source, a copper source, an iron source and a manganese source, and wet-milling them at a speed of 1400 rpm for 2 h until they are uniform (the wet-milling adopts an alumina ball milling jar and the ball milling medium is acetone), to obtain a precursor powder, wherein the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source and manganese in the manganese source is 0.7035:0.06:0.33:0.61, based on the amount of substance, the sodium source is sodium carbonate, the copper source is copper oxide (CuO), the iron source is iron oxide (Fe2O3), and the manganese source is manganese oxide (Mn2O3);

[0075] S2, placing the precursor powder in a muffle furnace, heating it to 900°C at a rate of 5°C / min in an air atmosphere and sintering it at 900°C for 12 h, and then cooling it to room temperature 20-25°C with the furnace to obtain a sodium ion battery positive electrode material.

[0076] Comparative Example 2

[0077] A sodium ion battery positive electrode material (Na 0.67 Cu 0.06 Fe 0.33 Mn 0.53 Al 0.08 O2) preparation method, comprising the following steps:

[0078] S1, mixing a sodium source, a copper source, an iron source, a manganese source and an aluminum source, and wet-milling them at a rotation speed of 1400 rpm for 2 h until they are uniform (the wet-milling adopts an alumina ball milling jar and the ball milling medium is acetone), to obtain a precursor powder, wherein the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, manganese in the manganese source and aluminum in the aluminum source is 0.7035:0.06:0.33:0.53:0.08 in terms of the amount of substance, the sodium source is sodium carbonate, the copper source is copper oxide (CuO), the iron source is iron oxide (Fe2O3), the manganese source is manganese oxide (Mn2O3), and the aluminum source is aluminum oxide (Al2O3);

[0079] S2, placing the precursor powder in a muffle furnace, heating it to 900°C at a rate of 5°C / min in an air atmosphere and sintering it at 900°C for 12 h, and then cooling it to room temperature 20-25°C with the furnace to obtain a sodium ion battery positive electrode material.

[0080] Comparative Example 3

[0081] A sodium ion battery positive electrode material (Na 0.67 Cu 0.06 Fe 0.33 Mn 0.53 Li 0.08 O2) preparation method, comprising the following steps:

[0082] S1, mixing a sodium source, a copper source, an iron source, a manganese source and a lithium source, and wet-milling them at a rotation speed of 1400 rpm for 2 h until they are uniform (the wet-milling adopts an alumina ball milling jar and the ball milling medium is acetone), to obtain a precursor powder, wherein the ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, manganese in the manganese source and lithium in the lithium source is 0.7035:0.06:0.33:0.53:0.084 in terms of the amount of substance, the sodium source is sodium carbonate, the copper source is copper oxide (CuO), the iron source is iron oxide (Fe2O3), the manganese source is manganese oxide (Mn2O3), and the lithium source is lithium carbonate (Li2CO3);

[0083] S2, placing the precursor powder in a muffle furnace, heating it to 900°C at a rate of 5°C / min in an air atmosphere and sintering it at 900°C for 12 h, and then cooling it to room temperature 20-25°C with the furnace to obtain a sodium ion battery positive electrode material.

[0084] Examples 3-4 and Comparative Examples 4-6

[0085] A method for preparing a sodium ion battery comprises: in a glove box, assembling a positive electrode shell, a positive electrode sheet, a diaphragm, a negative electrode sheet, a gasket, a spring, and a negative electrode shell in order to obtain a sodium ion battery, wherein the electrolyte in the electrolyte used in the sodium ion battery is NaClO4, and the concentration of the electrolyte in the electrolyte is 1 mol L -1 The solvent in the electrolyte is a mixture of propylene carbonate (PC) and fluoroethylene carbonate (FEC), and the ratio of propylene carbonate to fluoroethylene carbonate is 95:5 by volume. The negative electrode sheet is a sodium sheet, and the separator is a glass fiber. The method for obtaining the positive electrode sheet is: the positive electrode material, the conductive agent (acetylene black) and the binder solution (the binder solution is a mixture of PVDF and N-methylpyrrolidone, and the concentration of PVDF in the binder solution is 20 mg mL -1) are mixed evenly to obtain a slurry, the slurry is evenly coated on an aluminum foil, dried in a vacuum oven at 80 ° C for 12 hours, cut into circular electrode sheets with a diameter of 12 mm using a sheet cutter (the loading amount of the slurry on the circular electrode sheet with a diameter of 12 mm is 1.5 mg), and then the circular electrode sheet is pressed at a pressure of 10 MPa for 30 s using a tablet press to obtain a positive electrode sheet, wherein the ratio of PVDF in the positive electrode material, the conductive agent and the binder solution is 8:1:1 by mass. The positive electrode material is one of the high cycle stability sodium ion battery positive electrode materials prepared in Examples 1 to 2 and the sodium ion battery positive electrode materials prepared in Comparative Examples 1 to 3.

[0086] Table 2

[0087]

[0088] Example 1 The XRD pattern of the prepared high cycle stability sodium ion battery positive electrode material is as follows Figure 1 As shown, Figure 1 The XRD patterns of P2-type layered Na 0.7 MnO 2.05 match( P 63 / mmc , JCPDS NO. 27-0751), the high cycle stability sodium ion battery positive electrode material prepared in Example 1 is P2 phase.

[0089] Example 1 SEM of the prepared high cycle stability sodium ion battery positive electrode material Figure 2 As shown, through SEM observation, the high cycle stability sodium ion battery positive electrode material prepared in Example 1 is a layered structure.

[0090] The charge and discharge curve of the sodium ion battery prepared in Example 3 is as follows Figure 3 As shown by Figure 3 It can be seen that the sodium ion battery prepared in Example 3 has a current density of 140 mAh g at 2-4.2 V and 0.2 C. -1 The discharge capacity.

[0091] The sodium ion battery prepared in Example 3 was subjected to charge and discharge tests. The sodium ion battery prepared in Example 3 had a charge and discharge capacity of 121 mAh g at 2-4.2 V and 1 C current density. -1 The discharge capacity.

[0092] Example 3 The cycle performance of the sodium ion battery prepared at a current density of 1 C is as follows Figure 4 As shown, the initial discharge capacity is 121 mAh g -1 After 100 cycles, the discharge capacity is 119 mAh g -1 , the capacity retention rate is 98%.

[0093] Example 3 The cycle performance of the sodium ion battery prepared at a current density of 2 C is as follows Figure 5 As shown, the initial discharge capacity is 95 mAh g -1 After 200 cycles, the discharge capacity is 83 mAh g -1 , the capacity retention rate is 87%.

[0094] Example 3 The cycle performance of the sodium ion battery prepared at a current density of 5 C is as follows Figure 6 As shown, the initial discharge capacity is 70 mAh g -1 After 500 cycles, the discharge capacity is 58 mAh g -1 , the capacity retention rate is 82%.

[0095] Example 3 The cycle performance of the sodium ion battery prepared at a current density of 10 C is as follows: Figure 7 As shown, the initial discharge capacity is 62 mAh g -1 After 1000 cycles, the discharge capacity is 62 mAh g -1 , the capacity retention rate is 100%.

[0096] Example 2 XRD of the prepared high cycle stability sodium ion battery positive electrode material Figure 8 As shown, Figure 8 The XRD patterns of P2-type layered Na 0.7 MnO 2.05 match( P 63 / mmc , JCPDS NO. 27-0751), the high cycle stability sodium ion battery positive electrode material prepared in Example 2 is P2 phase.

[0097] Example 2 SEM of the prepared high cycle stability sodium ion battery positive electrode material Fig. 9 As shown, through SEM observation, the high cycle stability sodium ion battery positive electrode material prepared in Example 2 is a layered structure.

[0098] The charge and discharge curve of the sodium ion battery prepared in Example 4 is as follows Fig.10 As shown, the sodium ion battery prepared in Example 4 has a capacity of 143 mAh g at 2-4.2 V and 0.2C current density. -1 The discharge capacity.

[0099] The sodium ion battery prepared in Example 4 was subjected to charge and discharge tests. The sodium ion battery prepared in Example 4 had a charge and discharge capacity of 115 mAh g at 2-4.2 V and 1C current density. -1 The discharge capacity.

[0100] Example 4 The cycle performance of the sodium ion battery prepared at a current density of 0.5 C is as follows Fig.11 As shown, the initial discharge capacity is 113 mAh g -1 After 100 cycles, the discharge capacity is 101 mAh g -1 , the capacity retention rate is 89%.

[0101] Example 4 The cycle performance of the sodium ion battery prepared at a current density of 1 C is as follows Fig.12 As shown, the initial discharge capacity is 108 mAh g -1 After 100 cycles, the discharge capacity is 100 mAh g -1 , the capacity retention rate is 93%.

[0102] The XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 1 is as follows: Fig.13 As shown, Fig.13 The XRD patterns of P2-type layered Na 0.7 MnO 2.05 match( P 63 / mmc , JCPDS NO. 27-0751), the sodium ion battery positive electrode material prepared in Comparative Example 1 is P2 phase.

[0103] Comparative Example 1: SEM of the sodium ion battery positive electrode material prepared Fig.14 As shown, through SEM observation, the sodium ion battery positive electrode material prepared in Comparative Example 1 has a layered structure.

[0104] The charge and discharge curve of the sodium ion battery prepared in Comparative Example 4 is as follows: Fig.15 As shown, the sodium ion battery prepared in Comparative Example 4 has a capacity of 117.5 mAh g at 2-4.2 V and 1 C current density. -1 The discharge capacity.

[0105] The cycle performance of the sodium ion battery prepared in Comparative Example 4 at a current density of 1 C is as follows: Fig.16 As shown, the initial discharge capacity is 117 mAh g -1 After 100 cycles, the discharge capacity is 81 mAh g -1 , the capacity retention rate is 69%.

[0106] The XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 2 is as follows: Fig.17 As shown, Fig.17 The XRD patterns of P2-type layered Na 0.7 MnO 2.05 match( P 63 / mmc, JCPDS NO. 27-0751), the sodium ion battery positive electrode material prepared in Comparative Example 2 is P2 phase.

[0107] Comparative Example 2 SEM of the sodium ion battery positive electrode material prepared Fig.18 As shown, through SEM observation, the sodium ion battery positive electrode material prepared in Comparative Example 2 has a layered structure.

[0108] The charge and discharge curve of the sodium ion battery prepared in Comparative Example 5 is as follows: Fig.19 As shown, the sodium ion battery prepared in Comparative Example 5 has a capacity of 112.5 mAh g at 2-4.2 V and 1 C current density. -1 High discharge specific capacity.

[0109] The cycle performance of the sodium ion battery prepared in Comparative Example 5 at a current density of 1 C is as follows: Fig. 20 As shown, the initial discharge capacity is 112 mAh g -1 After 100 cycles, the discharge capacity is 81 mAh g -1 , the capacity retention rate is 72%.

[0110] The XRD pattern of the sodium ion battery positive electrode material prepared in Comparative Example 3 is as follows: Fig.21 As shown, Fig.21 The XRD patterns of P2-type layered Na 0.7 MnO 2.05 match( P 63 / mmc , JCPDS NO. 27-0751), the sodium ion battery positive electrode material prepared in Comparative Example 3 is P2 phase.

[0111] Comparative Example 3: SEM of the sodium ion battery positive electrode material prepared Fig. 22 As shown, through SEM observation, the sodium ion battery positive electrode material prepared in Comparative Example 3 has a layered structure.

[0112] The charge and discharge curve of the sodium ion battery prepared in Comparative Example 6 is as follows: Fig.23 As shown, the sodium ion battery prepared in Comparative Example 6 has a capacity of 113.3 mAh g at 2-4.2 V and 1 C current density. -1 The discharge capacity.

[0113] The cycle performance of the sodium ion battery prepared in Comparative Example 6 at a current density of 1 C is as follows: Fig.24 As shown, the initial discharge capacity is 117 mAh g -1 After 100 cycles, the discharge capacity is 99 mAh g -1 The capacity retention rate of the sodium ion battery prepared in Comparative Example 6 was 84% ​​after 100 cycles.

[0114] The discharge median voltage and energy density of the sodium ion batteries prepared in Examples 3-4 and Comparative Examples 4-6 are shown in Table 3.

[0115] Table 3

[0116]

[0117] In the electrochemical test, the discharge specific capacity and cycle stability of the embodiment are higher than those of the comparative example. The reason is that the inactive Li element not only stabilizes the lattice of the transition metal layer, but also buffers the lattice distortion caused by the valence change of the active element. At the same time, Li element doping can increase the valence state of Mn, thereby inhibiting the 3+ The Jahn-Teller effect. Inactive Al elements can be reduced by reducing Mn 3+ ratio, effectively inhibiting Na + The Jahn-Teller effect during the deintercalation process inhibits the deterioration of the P2-P2′ phase transition. Therefore, Li and Al co-doping can improve the capacity, discharge median voltage and cycle stability of the positive electrode material of sodium ion batteries.

[0118] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material for a sodium ion battery with high cycle stability, characterized in that it comprises the following steps: S1, mix the sodium source, copper source, iron source, manganese source, lithium source and aluminum source evenly to obtain a precursor powder. The ratio of sodium in the sodium source, copper in the copper source, iron in the iron source, manganese in the manganese source, lithium in the lithium source and aluminum in the aluminum source is 0.7035:0.06:0.33:(0.61-xy) by amount of substance: 1.05x:y, where x=0.08,y=0.08; S2, sintering the precursor powder at 600-1000 °C for 2-24 h, cooling with the furnace, and obtaining a positive electrode material for a sodium ion battery with high cycle stability. The sodium ion battery prepared from the positive electrode material for a sodium ion battery with high cycle stability has a discharge median voltage of 3.2 V and an energy density of 412.2 Wh kg -1 .

2. The preparation method according to claim 1, characterized in that: In S1, a sodium source, a copper source, an iron source, a manganese source, a lithium source and an aluminum source are mixed and wet-ball-milled to be uniform.

3. The preparation method according to claim 2, characterized in that: The rotation speed of the wet ball milling is 300-1400 rpm, and the time of the wet ball milling is 0.5-3 h.

4. The preparation method according to claim 3, characterized in that: In S2, the heating rate to 600~1000 ℃ is 3~5 ℃ / min.

5. A sodium ion battery positive electrode material with high cycle stability obtained by the preparation method according to any one of claims 1 to 4.

6. Use of the high cycle stability sodium ion battery positive electrode material as claimed in claim 5 in improving the discharge specific capacity of the sodium ion battery.

7. Use of the high cycle stability sodium ion battery positive electrode material as claimed in claim 5 in improving the median discharge voltage of the sodium ion battery.

8. Use of the high cycle stability sodium ion battery positive electrode material as claimed in claim 5 in improving the cycle stability of sodium ion batteries.

9. Use of the high cycle stability sodium ion battery positive electrode material as claimed in claim 5 in improving the energy density of sodium ion batteries.

10. A sodium ion battery comprising: The high cycle stability sodium ion battery positive electrode material as described in claim 5.

Citation Information

Patent Citations

  • Copper-iron-manganese-based positive electrode material for sodium-ion battery and preparation method thereof

    CN115611319A

  • Copper-manganese-based sodium ion battery positive electrode material and preparation method thereof

    CN116259742A